Quality Analysis of Web-Based Visitor Management System (DATENG) Using Cypress Testing and Task-Based Usability Testing Methods Based on ISO 9241-11 (Case Study of PT Perta Arun Gas) - Rizky Putra Fhonna; Yesy Afrillia; Ilham Sahputra; Sayed Fachrurrazi; Faiz Fadhilla (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
Manual management of visitor data in the company environment has the potential to cause various problems, such as time inefficiency, the risk of data loss, and the occurrence of physical queues during certain operational hours. These conditions can hinder the smooth running of operational activities and reduce the quality of service to guests. Therefore, a web-based visitor management system called DATENG was developed which aims to support the process of recording, scheduling, and verifying visits in an integrated and structured manner. This research activity focuses on testing and evaluating the quality of the DATENG system to ensure that the system can function properly and is easy to use by users. The method used consists of two main approaches, namely functionality testing and usability evaluation. Functionality testing is carried out using the Cypress Testing method with an end-to-end testing approach to verify that all system features are running according to the needs that have been set. Furthermore, usability evaluation is carried out using a task-based testing method based on the ISO 9241-11 standard, which includes measuring aspects of effectiveness, efficiency, and satisfaction. The test results show that all the key features of the DATENG system can function properly without significant functional errors being found. Usability evaluations show that users are able to complete each task with a high success rate, relatively efficient turnaround time, and a good level of user satisfaction. Based on these results, it can be concluded that the DATENG system has good system quality and is able to support the visitor management process effectively, efficiently, and provide a positive user experience in accordance with the company's operational context.